Cutoff scores for the “Interest game”, an application for the assessment of diminished interest in neurocognitive disorders - Manera, Valeria; Fabre, Roxane; Daumas, Lyne; Zeghari, Radia; Derreumaux, Alexandre; Payne, Magali; Lemaire, Justine; Sacco, Guillaume; Gros, Auriane; Robert, Philippe (Frontiers in Psychiatry, 2023)
Diminished interest is a core feature of apathy that shows high prevalence in people with Mild and Major Neurocognitive disorders (NCD). In the clinical setting, apathy is mainly assessed using clinical scales and questionnaires, but new technologies are starting to be employed to complement classical instruments. Here we explored the performance of the “Interest Game”, a ludic application that assesses personal interests, in discriminating between subjects with and without diminished interest based on the Apathy Diagnostic Criteria (ADC). 227 elderly participants (56 healthy controls, 118 persons with mild NCD, and 53 with major NCD) completed the Interest game and were assessed by clinicians concerning the presence and the severity of apathy. Results showed that the application scores varied with the presence of apathy, the type of disorder, and the education level. Cutoff scores calculated for subjects with Mild NCD resulted in a sensitivity of 0.68 and a specificity of 0.65 for the main score index, suggesting the interest of employing this application in the clinical setting to complement the classical assessment.